The Influence Of Herding And Overconfidence On Investment Decisions: The Moderating Role Of Risk Perception Among Investors In Surabaya - Yustiawan, Arealdo Robiq; Anwar, Muhadjir (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study analyzes the influence of herding and overconfidence on investment decisions, with risk perception as a moderating variable among young investors in Surabaya. A quantitative method was used with 100 purposively selected respondents. Data were gathered through structured questionnaires and analyzed using PLS-SEM via SmartPLS 4.0. Results show that herding and overconfidence significantly and positively influence investment decisions. However, risk perception does not moderate the effect of herding, indicating that social factors may outweigh individual risk awareness. In contrast, risk perception significantly weakens the impact of overconfidence, suggesting that risk-aware investors are more cautious and rational. These findings align with the Theory of Planned Behavior, emphasizing the role of perceived behavioral control. The study highlights the importance of addressing behavioral biases and risk perception in financial education to support better investment decision-making.